Is Hemodialysis Patient Survival Dependent upon Small Solute Clearance (Kt/V)?: If So How Can Kt/V be Adjusted to Prevent Under Dialysis in Vulnerable Groups?. Issue 2 (11th January 2017) - Davenport, Andrew
Abstract: Small solute clearance achieved during a single hemodialysis session has been traditionally evaluated by urea clearance, normalized for total body water ( Kt / V urea) for more than 30 years. By consensus, the target sessional KtV urea for thrice weekly treatments has been increased from 0.9 to 1.2 over the years. Although this is supported by observational studies, there is a fundamental lack of prospective studies to support this threshold target. In clinical practice achieving sessional Kt / V urea targets are most closely followed in the US. Yet there appears to be a paradox in that by following Kt / V urea targets in the US hemodialysis patient survival is better for men and the obese, the opposite of what is seen in the general population. Delivery of a lower dose of hemodialysis to women and smaller men can be explained by underestimation of total body water. The advent of bioimpedance techniques which can measure both body water and body composition will potentially allow a rescaling and re‐evaluation of the importance of small solute clearances ( Kt / V urea) in the hemodialysis patient population.